Opinion 2461: Iberolacerta Arribas, 1999 and Darevskia Arribas, 1999 (Chordata, Squamata, Lacertidae): names confirmed as available - ICZN (Bulletin of Zoological Nomenclature, 2020)
The International Commission on Zoological Nomenclature has conserved the names Iberolacerta and Dareskia for two genera of lacertid lizards by confirming their availability from Arribas (1999). The microfiche publication (Arribas, 1997) is confirmed as unavailable and placed on the Official Index of Rejected and Invalid Works in Zoological Nomenclature. The name Caucasilacerta Harris, Arnold & Thomas, 1998 is confirmed as a nomen nudum and placed on the Official Index of Rejected and Invalid Generic Names in Zoology
Keywords: taxonomy; Squamata; LACERTIDAE; Iberolacerta; Darevskia; Caucasilacerta; Europe; Caucasus; Anatolia; Near East; microfiche edition; Nomenclature